Changes in rRNA Levels during Stress Invalidates Results from mRNA Blotting: Fluorescence In Situ rRNA Hybridization Permits Renormalization for Estimation of Cellular mRNA Levels - Hansen, Martin C. (American Society for Microbiology, 2001)
Regulation of gene expression can be analyzed by a number of different techniques. Some techniques monitor the level of specific mRNA directly, and others monitor indirectly by determining the level of enzymes encoded by the mRNA. Each method has its own inherent way of normalization. When results obtained by these techniques are compared between experiments in which differences in growth rates, strains, or stress treatments occur, the normalization procedure may have a significant impact on the results. In this report we present a solution to the normalization problem in RNA slot blotting experiments, in which mRNA levels routinely are normalized to a fixed amount of extracted total RNA. The cellular levels of specific mRNA species were estimated using a renormalization with the total RNA content per cell. By a combination of fluorescence in situ rRNA hybridization, which estimates the relative level of rRNA per cell, and slot blotting to rRNA probes, which estimates the level of rRNA per extracted total RNA, the amount of RNA per cell was calculated in a series of heat shock experiments with the gram-positive bacterium Lactococcus lactis. It was found that the level of rRNA per cell decreased to 30% in the course of the heat shock. This lowered ribosome level led to a decrease in the total RNA content, resulting in a gradually increasing overestimation of the mRNA levels throughout the experiment. Using renormalized cellular mRNA levels, the HrcA-mediated regulation of the genes in the hrcA-grpE-dnaK operon was analyzed. The hybridization data suggested a complex heat shock regulation indicating that the mRNA levels continued to rise after 30 min, but after renormalization the calculated average cellular levels exhibited a much simpler induction pattern, eventually attaining a moderately increased value.